RETRACTED: Kinesin Family Member 2A Serves as a Potential Biomarker Reflecting More Frequent Lymph Node Metastasis and Tumor Recurrence Risk in Basal-Like Breast Cancer Patients - Yang, Hua; Liu, Yongjun (Frontiers in Surgery, 2022)
Background: Kinesin family member 2A (KIF2A) is reported as an oncogene and a potential biomarker for progression and prognosis in several cancers such as cervical, ovarian, gastric cancers, etc. However, its clinical value in basal-like breast cancer (BLBC) is unclear. This study aimed to evaluate KIF2A expression and its correlation with clinical features and survivals in BLBC patients. Methods: KIF2A mRNA and protein expressions in the tumor and adjacent tissues from 89 BLBC patients were assessed by reverse transcription-quantitative polymerase chain reaction and immunohistochemistry assays, respectively. Results: Both KIF2A protein (P<0.001) and mRNA expressions (P<0.001) were higher in tumor than in adjacent tissue. Besides, tumor KIF2A protein expression was positively correlated with N (P=0.028) and TNM (P=0.014) stages; meanwhile, tumor KIF2A mRNA expression was positively correlated with N stage (P=0.046), TNM stage (P=0.006) and tumor size (P=0.043). Additionally, tumor KIF2A protein (P=0.035) and mRNA (P=0.039) high expressions were both correlated with worse disease-free survival (DFS), but not overall survival (OS) (both P>0.05). Moreover, tumor KIF2A protein expression was higher in relapsed patients than in non-relapsed patients within 3 years (P=0.015) and 5 years (P=0.031); whereas, no difference was discovered between deaths and survivors within 3 years (P=0.057) or 5 years (P=0.107). Lastly, after adjustment, tumor KIF2A mRNA high exhibited a trend to be correlated with DFS but without statistical significance (P=0.051). Conclusion: KIF2A correlates with more frequent lymph node metastasis and worse DFS in BLBC patients, shedding light on its potency as a biomarker for BLBC.